Sedentary behavior, cognition, and brain health in older adults: a systematic review - Gogniat, Marissa A.; Won, Junyeon; Cruz, Carlos; Aranda, Amaya; Verma, Aryan; Gujral, Swathi; Weinstein, Andrea M.; Zaheed, Afsara B.; Cole, Keith R.; Full, Kelsie M.; Snitz, Beth E. (Frontiers in Aging Neuroscience, 2025)
Sedentary behavior has been associated with poor health outcomes, especially in older adulthood. Given that sedentary behavior is a highly prevalent, modifiable health behavior, there has been a recent increased interest in examining how sedentary behavior relates to cognition and brain health. The current body of literature is limited and mixed. The purpose of this systematic review was to examine the associations of sedentary behavior with cognition and brain health in older adults across the cognitive spectrum. This study was pre-registered with PROSPERO (CRD42023477868). Six comprehensive databases were searched with pre-registered search terms. A total of 33 studies were included. Overall, results indicated that greater sedentary behavior was associated with worse cognition and brain health, although associations varied based on differences in measurement and classification of sedentary behavior. We discuss next steps and implications for future research.